2015
DOI: 10.5006/1757
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Cold Spray Deposited Copper Coating on Steel Substrates

Abstract: The corrosion behavior of copper cold spray coatings on a carbon steel substrate was compared to that of commercially available wrought copper under the conditions anticipated in a nuclear waste repository. Corrosion potential and linear polarization resistance measurements were conducted over 90 d to 120 d in 3.0 mol/L NaCl under anoxic (1) and oxygenated-toanoxic (2) conditions to simulate the long (1) and short (2) term redox conditions expected in a Canadian repository. Scanning electron microscopy and x-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The application of EBSD will help to optimize the choice of coating parameters required to satisfy mechanical design requirements and to identify the microstructural features which could be important in determining corrosion rates. A detailed study of the corrosion performance of these coatings are published elsewhere [23].…”
Section: Introductionmentioning
confidence: 99%
“…The application of EBSD will help to optimize the choice of coating parameters required to satisfy mechanical design requirements and to identify the microstructural features which could be important in determining corrosion rates. A detailed study of the corrosion performance of these coatings are published elsewhere [23].…”
Section: Introductionmentioning
confidence: 99%
“…During the same time, R p increased to an approximate steady‐state value ~10 2 times greater than that achieved under aerated conditions, confirming a major drop in the corrosion rate when the availability of oxygen was limited. In anoxic solutions, when the oxygen concentration would be ~10 −9 M, [ 24 ] E corr was approximately the same as in the aerated solution, before decreasing slowly to a value less than that observed in argon‐sparged conditions. This decrease was accompanied by an increase in R p to a value ~3 times than that observed under argon‐sparged conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This raises concerns about whether the PPIs in CS materials, where the oxide inclusions universally exist, are prone to corrosion especially under aggressive environments. Despite most studies' revealing unremarkable to marginally increased corrosion damage at the PPIs [13][14][15][16], a recent study [17] showed that CS Cu, a candidate for the corrosion-resistant coa�ng of Canadian-designed used nuclear fuel containers (UFCs) [17], exhibited higher degree of reac�vity at the PPIs when exposed to naturally aerated dilute nitric acid (HNO3) solu�on [18]; however, the exact corrosion mechanism was not inves�gated. Previous studies have shown that dissolved oxygen is paramount in the corrosion of the wrought Cu in dilute HNO3 solu�ons [19][20][21].…”
Section: Introduc�onmentioning
confidence: 99%